'Green' practices and value co-creation: does guest culture make a difference?. Issue 1 (31st December 2023) - Ruiz-Molina, María Eugenia; Gil-Saura, Irene; Moise, Mihaela Simona; Marín-García, Antonio
Abstract: In an increasingly competitive environment, many hotels have implemented sustainable practices and have actively involved the guests in the generation of unique experiences through the value co-creation process. In this sense, this paper aims at analysing the impact of 'green' practices and value co-creation on hotel image, guest trust, satisfaction, and loyalty, and to assess the moderating role of culture, conceived as related to guest nationality. To test the model, a quantitative method based on a sample of 611 guests from Spain and Colombia was used. Our results indicated that there are significant differences based on the guests´ nationality regarding the effects of value co-creation and image on trust, image on satisfaction, and satisfaction on loyalty. These findings will allow hotel management to have a better understanding of tourists when designing their corporate strategies.